Alterações hidroquímicas em reservatórios do semiárido cearense - Batista, Ana Carolina de Oliveira Nobre (2019)
Constant climatic variations promote changes in aqueous ionic content and water quality, modifying the original reservoir hydrochemistry in semiarid regions. Previous studies have focused on observing the mechanisms of ion exchange only in groundwater, not exploring the hydrochemistry of surface water, which makes this line of research deficient. Thus, this work aims to investigate the quality of surface water concerning the ionic content and the dominant mechanisms of origin and ion exchange in four reservoirs of Ceará semiarid, observing the hydroclimatic relations. The areas object of the study were divided between the Banabuiú basins (Banabuiú and Pedras Brancas reservoirs), Curu basin (Pentecoste) and Serra da Ibiapaba basin (Jaburu I reservoir). The research parameters were divided into general (ratio between available volume, larger ions), hydrochemical (classification according to Piper, Gibbs and Chadha and ionic ratios), ionic (Langelier Saturation Stability Index, Aggressiveness and Ryznar Stability), climatic (Lang index) and hydroclimatic (ionic ratios versus available volume, volumetric precipitation and Lang index). During the analyzed period, salinization occurred in all reservoirs, with different hydrochemical classifications: Banabuiú presented mixed bicarbonated waters and Pedras Brancas, Pentecoste and Jaburu I sodium chlorinated waters. According to the ionic indices, Banabuiú waters can be classified as mild scale, strong corrosion. White Stones had their waters characterized as strong and smooth fouling, strong and moderate corrosion, without aggression and with low risk of sodicity. The Pentecost reservoir has been defined as mild scale, strong corrosion, no aggression and low sodium risk. Jaburu I surface waters were indicative of mild fouling and severe corrosion, moderately aggressive, with low sodium risk. According to the Lang index calculation, the four reservoirs studied presented climatic aridity. The hydroclimatic approach was important to highlight the positive correlation between some ionic ratios analyzed and the percentage of available water volume. It is concluded that the study of hydroclimatic variability interferes in the hydrochemical parameters, being essential the verification of the interconnections related to the ionic content and the hydrogeology of the reservoirs.